Development of Kanom Babin with Perilla Seeds - พุกเนียม พรกรัณย์; พรหมเสน พีระพันธ์; เมฆวิลัย ราตรี (Journal of Thai Food Culture, 2021)
This study aimed to develop Kanom Babin added Perilla seed known as a local material from the northern part of Thailand. One recipe of Kanom Babin was selected from 3 recipes and studied on levels of Perilla seeds. Then, preference of 120 customers were evaluated by 9-point hedonic scale. ANOVA was used to test the mean difference via Duncan’s New Multiple Rang Test (DMRT) with the statistical significance of .05. Results demonstrated that Kanom Babin recipe 2 with 10% Perilla seed demonstrated the slightly to like moderately preference by its color and texture (6.87, 6.99 respectively). The fagrance, taste, crispiness, softness and overall preference were moderately to extremely (7.27, 7.13, 7.32, 7.04 and 7.26 respectively). Production cost per piece was 0.78 Baht and price per box (5 pieces; 75-80 grams) was 20 Baht. The investigation of product benefit revealed that Kanom Babin with 10% Perilla seed (85 grams) were rich of nutrition; protein (27.1 g), fat (45.4 g), carbohydrate (63.9 g), calcium (603 mg), and phosphorus (56 mg).